Upaya Meningkatkan Minat Membaca Pada Anak Kelas 4 Sd - Ananta Pramayshela; Erma Yanti Tanjung; Fitri Yantu Pasaribu; Rinanti Ito Pohan (Pusat Riset dan Inovasi Nasional, 2023)
Reading is a language skill that must be possessed by everyone to broaden knowledge, experience, sharpen reasoning, enhance thinking and to achieve the goals of the times. to get information about written topics The lack of student interest in reading causes difficulties in carrying out learning even though interest in reading also increases if students themselves, teachers and parents have maturity, desire and encouragement In the form of reading, curiosity about something that everyone is interested in gets an answer to Mirat's question, mambuca is a strong and deep concern accompanied by a sense of pleasure in reading, so that nawa individuals are guided to read everything with their will and desire. Saudi pastala or library can be interpreted as a series of activities related to the method of collecting pasta data, reading and recording and processing research haha Literature studies can also study various reference books and similar previous research results which are useful for obtaining theoretical foundations regarding the problem to be studied. Specific reading requires reading for study purposes (scientific analysis) reading for the purpose of capturing the outline of the reading.